Hierarchical approach of mitigating carbon influence in nano-porous electro-catalyst with unique surface islands for efficient methanol resistive oxygen reduction. (1st February 2018) - Anandha ganesh, P.; Jeyakumar, D.
Abstract: For the first time, we report a facile one pot aqueous method for support-free Pd85 Pt15 nano-porous structures (NPoS) synthesis from PdMn nano-alloys at ambient conditions. A hierarchical approach was successfully employed through a simple "self-settlement" process with descending amounts of carbon to carbon-free electro-catalysts to improve catalyst utilization and avoid carbon degradation during fuel cell operating conditions. Pd85 Pt15 NPoS exhibits enhanced methanol resistive oxygen reduction reaction (ORR) activity owing to the presence of highly active and unique surface PdPt islands compared to HiSPEC Pt/C catalysts. Accelerated durability tests of the support-free PdPt NPoS show enhanced durability in harsh acidic environment (1.0 N H2 SO4 ) compared to HiSPEC Pt/C and DOE 2017–2020 durability target. Preliminary direct methanol fuel cell studies using hierarchically derived Pd85 Pt15 NPoS variants were performed at ultra-low Pt content. The effects of carbon content and catalyst layer thickness on fuel cell activities are well discussed. Graphical abstract: Image 1 Highlights: Facile and novel one pot aqueous synthesis of support free nano-porous Pd85 Pt15 electro-catalysts from PdMn nano-alloy. Exhibits enhanced methanol resistive oxygen reduction activity owing to the presence of surface active Pd-Pt nano-islands. Accelerated durability tests shows excellent stability in 1.0 N H2 SO4 electrolyte. Direct methanol fuel cell studies shows a highest power density (85 mWmg −1 Pt cm −2 ) at ultra-low total Pt content.